Faith, gift and commitment - Latorre Ariño, Marino (2018)
This article is about faith and religious beliefs, their meaning and the rational possibility of religious fact. Arguments are raised and discussed for and against the act of faith. The possibility and characteristics of the act of faith are described and the appropriate and inadequate positions before the Absolute are analyzed. Reason and faith are the two wings with the human spirit rising towards the contemplation of the truth. The conclusion is that "Hidden God" might only be known through the experience of personal faith --Nihil intelligitur nisi diligitur-- (you only understand what you love) by Saint Augustine.